Product Lifecycle Management - Saaksvuori, Antti; Immonen, Anselmi (Springer Berlin Heidelberg : Imprint: Springer, 2008)
The significance of product lifecycle management (PLM - Product Lifecycle Management, formerly referred to, in a narrower frame of reference, as PDM - Product Data Management) is increasing, especially for companies in the manufacturing, high technology, and service industries. Product and component lifecycles are shortening while, at the same time, new products must be delivered to market more quickly than before. Many manufacturing and service companies are also trying to grow out of a bulk provider role. In the future they will be p- viding configurable and flexible solutions rather than just individual products. This leads companies to form networks in which each actor specializes in the planning, manufacture or integration of products in a certain field. Information concerning common products must pass quickly, faultlessly, and automatically between companies so that they can compete effectively in international markets. In today's industrial production, therefore, PLM is an essential tool for coping with the challenges of more demanding global competition and ever-shortening product and component lifecycles and growing customer needs. New, better and more flexible products must be introduced into markets more quickly, with more profit and less labor, and the lifecycle of each product must be better controlled, for example, from financial and environmental perspectives. Fierce competition in global markets drives companies to perform better. In order to perform well financially, companies must be able to make informed decisions concerning the lifecycle of each product in their portfolio.